VICTIMOLOGICAL COUNTERACTION TO CRIMINALITY: CONCEPTUAL ASPECTS OF CRIMINAL POLICY (Journal of actual problems of jurisprudence, 2018)
In this article, the authors draw attention to the victimological direction in the implementation of the criminal policy of the state.The purpose of this article is to investigate the conceptual aspects of the victimological policy of the state as one of the directions of the criminal policy in the field of combating crime.The very problem of criminal policy is a complex, systemic socio-political and legal problem of modern Kazakhstan, conditioned by general and special economic, political, spiritual, methodological, legal, criminological, criminological and other factors. Victimological policy is considered as one of the branch directions of criminal policy, a means of influencing crime in the mainstream of world trendsIn today’s Kazakhstan, a comprehensively developed theoretical and regulatory framework for the development of the system of victimological crime prevention, protection of the rights of victims and victims of crime has been formed. Meanwhile, in modern legal literature and in crime prevention practice, a point of view has been formed according to which the victimological direction is only part of the strategy and tactics of crime prevention and criminal legal protection of citizens. Numerous studies have not yet led to the development of a sufficiently accurate and complete picture of the victimological counteraction of crime as a sphere of criminal policy. This determines the novelty of this study. In the proposed article, the authors hold and disclose the position that in terms of content, subject matter of regulation, subjective composition, victimological policy in a certain sense is broader than the scientifically grounded strategy and tactics of crime prevention and regulation of criminal legal relations implemented in modern criminal policy.In the proposed article, based on the study and generalization of existing theoretical views, the essence of the conceptual approach to determining the victimological policy of the state in the sphere of combating crime is presented in a generalized form. The authors reflect scientifically substantiated provisions and conclusions about the theoretical foundations of victimological crime prevention, which determines the scientific significance of this article. In addition, the main problems on the topic and the main directions of their solution are identified, which determines its practical significance.The methodological basis of the research is the scientific provisions of criminal law and criminology on the nature of crime and criminality, their impact on the state and public security, victimization, victimization, victimology. In the course of research into the modern concept of determining the nature of victimological crime prevention, the conclusions are obtained through qualitative and quantitative analysis of social, legal, criminal-legal phenomena and processes.The legal analysis carried out by the authors makes it possible to provide recommendations for the definition of new promising areas of Kazakhstan’s criminal policy in the sphere of combating crime, it can contribute to the solution and overcoming of the international aspect in the field of victim crime prevention, which requires the establishment of cooperation with other states.The results obtained in this article can be used in the educational process, for writing textbooks or teaching aids and publishing articles on this topic.Key words: criminality, crime prevention, criminal policy, victimology policy, victimality, victimization, the victim of crime.